From ethical guidance to practice: Oversight of quality improvement activities at Denver Health, a learning health system - Hasnain‐Wynia, Romana; Everhart, Rachel; Wittmer, Nancy; Podewils, Laura J.; MacKenzie, Thomas D. (Learning health systems, 2025)
Introduction A learning health system (LHS) strives to improve clinical practice and outcomes through applied research and quality improvement (QI). However, distinguishing between research and QI has been a persistent challenge. While research involving human subjects is highly regulated, QI remains largely unregulated, lacking in comparable oversight. With confusion and uncertainty surrounding this distinction and little practical guidance for QI activities, Denver Health's LHS developed a model of practice for reviewing QI projects. Methods In 2018, Denver Health, an integrated academic safety‐net delivery system, established the Quality Improvement Review Committee (QuIRC) as a practical approach for distinguishing between QI and human subjects research. We describe the institutional structure and processes, from identifying the problem to establishing the committee and charter, to obtaining institution support, and finally implementation and improvement, ensuring transparency and protections of disseminated QI work. Results Over 7 years, the QuIRC has reviewed 379 submissions, with 78% approved as QI (non‐human subjects research), 8% referred to the Colorado Multiple Institutional Review Board, and 13% requiring clarification or being withdrawn. A standardized review process, clear charter, broad organizational representation, executive sponsorship, and IRB collaboration enhanced transparency and engagement. The QuIRC has facilitated QI dissemination, supporting the LHS framework and increasing recognition of the impact of QI on clinical care and patient outcomes. Conclusions The QuIRC framework has improved clarity and oversight of QI activities at Denver Health. These practical approaches can be adapted by other health care systems, contributing to broader efforts to establish national guidance for QI oversight.